Acute ischemic stroke: extending the time window - Donnan, Geoffrey A. (Japanese Journal of Stroke, 2007)
Acute stroke interventions for all forms of stroke which have been proven to be of benefit based on level 1 evidence include the management of patients in stroke units (ischaemic and haemorrhagic stroke), use of oral aspirin within 48 hours (ischaemic stroke only) and intravenous tPA within 3 hours of stroke onset (ischaemic stroke only). The most biologically effective treatment for acute ischemic stroke is intravenous tPA administered within 3 hours of symptom onset. However, despite the strong evidence supporting its effectiveness, only 2-4% of all stroke patients currently receive tPA. The main reasons for this seem to be the narrow window of opportunity for treatment (3 hours) and the increased risk of haemorrhage. Hence, extending this brief therapeutic time window for thrombolysis as well as other forms of therapy is an important means by which patient's outcomes may be improved. The rationale for extending the therapeutic window is based on our understanding of the ischaemic penumbra which is known to exist for up to 48 hours in some individuals. The means of salvaging this tissue over this time period is the subject of ongoing basic and clinical research. The general strategies which may be adopted to salvage brain tissue at later time periods include: 1. Further enhancing recanalization and reperfusion within the life of the penumbra using intravenous and intra-arterial thrombolytic agents, combined routes, newer thrombolytic and antiplatelet agents as well as devices to improve revascularisation. 2. Selecting patients based on imaging techniques. This allows patients with persistent penumbra to be selected such as with the EPITHET trial using tPA within 3-6 hour time window, DIAS and DEDAS using desmoteplase with a 3-9 hour time window. 3. Freezing or prolonging the penumbra using neuroprotectants. Trials in which neuroprotectants alone have been used such as the recently reported NXY-059 studies have been disappointing. A new approach to neuroprotection is required in which reperfusion is an essential part of the study design. By extending the time window for therapy, the number of patients available for therapeutic intervention will be greater, thus making acute therapies more generalisable and more likely to have an impact on reducing the burden of stroke.